Prevalence of Virulence Genes and Antibiotic Resistance in Clinical Isolates of Proteus mirabilis - Marwa Shaker Mahmood; Mustafa S. AL-Salmani; Shahad Basil Ismael; Ahmed Sami AL-Salmany; Aws Akram Jumaah; Hasan A. Aal Owaif (International Journal of Biomedicine)
Background: Proteus mirabilis can be distributed in water, soil, and the human digestive tract. It is considered among the leading causes of urinary tract infections and can also cause bacteremia, as well as wound and respiratory infections. This study aimed to determine the antibiotic resistance profile and the number of virulence genes in local P. mirabilis isolates from various clinical samples. Methods and Results: Between May 2024 and August 2024, a total of 250 samples were collected from various clinical sources, including wound swabs, sputum, urine, and pus, at different hospitals in Baghdad. To identify P. mirabilis isolates, biochemical tests and the VITEK 2 system were used. An antibiotic susceptibility test was performed using the disc diffusion technique. The zapA, ureC, mrpA, and rsbA genes were detected by PCR. Seventy-three (29.2%) isolates out of 250 samples from different sources were identified as P. mirabilis. The results indicated that 73.6%, 29.3%, 6.2%, and 17.6% of pus, wound, sputum, and urine samples, respectively, were P. mirabilis. Of the isolates, 95.9% were resistant to nitrofurantoin, 75.3% to aztreonam, 91.8% to ampicillin, 67.1% to levofloxacin, 58.9% to ceftazidime, 52.1% to piperacillin, 27.4% to ciprofloxacin,11.0% to imipenem, and 9.6% to amikacin. The rate of zapA, ureC, mrpA, and rsbA genes was 75.3%, 91.7%, 52.1%, and 79.4%, respectively. Conclusion: This study showed that P. mirabilis is commonly found in sputum, urine, wounds, and pus samples, and that infections are more prevalent in men. It exhibits significant levels of antibiotic resistance, especially to nitrofurantoin (95.9%). The need for efficient infection control and antimicrobial stewardship to address multidrug-resistant P. mirabilis infections is highlighted by the rising antibiotic resistance, which has been linked to changes in bacterial enzymes and antibiotic misuse.